(untitled) (Economic and Political Thought, 2019)
This article is in fact a report from the discussion panel organised on 18 September 2018 during the Fourth National Political Science Congress entitled The State in Times of Change. As part of the Congress, Professor Józef M. Fiszer from the Institute of Political Studies of the Polish Academy of Sciences, organised an interesting panel entitled ‘Poland’s Foreign Policy in Times of Change in Europe and the World in the Twenty-First Century: Directions, Goals, Forms, Opportunities and Threats’. Panellists, outstanding specialists, who took part in it discussed goals, tasks, opportunities and threats for Polish foreign policy in the twenty-first century. During the discussion numerous interesting, theoretically and practically significant theses and hypotheses were formulated. They are presented and analysed in this article.